Non-work obligations : on the delicate art of dealing with disagreeableness - Stebbins, Robert A. (Emerald Publishing Limited, 2021)
The world of non-work obligations - defined as disagreeable activities that are neither work nor leisure - is a territory of social life that has largely been ignored by scholars of work and leisure alike. The exception to this rule is Robert A. Stebbins, who over the years has written extensively on the significance of non-work obligations and the mundane and often disagreeable tasks that we are all compelled to face in our daily lives. In this new book, Stebbins brings together years of writing and research on this topic to forcefully argue that the current research interest in work-life balance can no longer afford to ignore the effects that non-work obligation has on it. He contends that, whether we like it or not, non-work obligations bear heavily on both our work and leisure. Having to deal with disagreeable tasks and objectionable people on a daily basis, without the support of any outside agency, can seriously undermine our well-being, and it is only through recourse to voluntary simplicity that we can hope to limit the harmful impact of non-work obligations. Written both as a guide to happy living and as a powerful rejoinder to conventional orthodoxy in the fields of leisure and work studies, the book is essential reading for both the general reader and scholars of leisure, consumer, work and happiness studies.
Includes index.
Keywords: Social participation -- Psychological aspects.; Contentment.; Well-being.; Work-life balance.; Psychology -- Social Psychology.; Occupational & industrial psychology.; elektronické knihy; electronic books